CRITICAL REVIEW OF PARAMEDIC MEDICAL ASSISTANT DRIVER TRAINING PROGRAMS IN ASSESSING CURRICULUM EFFECTIVENESS, DRIVER SAFETY PROTOCOLS, AND EMERGENCY RESPONSE COORDINATION - Hassan Hussain Almakrami, Fehaid Ali Bani Humayyim, Mohammed Hussien Binhamim, Abdulrahman Salem Mohammed, Taher Saeed Mansour Alyami, Saeed Jarallah Mohammed Alqahtani, Masood Shtfan Salem Almutlaq, Mahdi Saad Mahdi Leslom (Chelonian Research Foundation, 2022)
Known as the Paramedic Medical Assistant Driver Education Program, these educational programs are necessary for ensuring the skills and expertise of emergency medical services (EMS) workers are as they need to be in terms of providing prompt and adequate care in the event of emergencies. This article critically examines the effectiveness of training programs produced by the ICUCA regarding curriculum design, driver safety protocols, and emergency coordination. This research paper walks through a literature review and scientifically proven data. It will determine the strengths and weaknesses of the current training program and recommend ways for institutions to improve its effectiveness. Research shows that including practical skills training, focusing on driver safety measures, and conducting effective communication and coordination among EMS specialists brings incredible benefits. Keywords: medical emergency response, paramedics and medical assistants; driver training programs; curriculum; driver safety protocols; and emergency response.